Pore Fractal Characteristics of Lacustrine Shale of Upper Cretaceous Nenjiang Formation from the Songliao Basin, NE China - Tian Dong; Lei Kang; Yifan Zhang; Yuan Gao (Applied Sciences, 2023)
The evaluation of pore characteristics in lacustrine shales is of significance for shale oil and gas exploration in terrestrial sedimentary basins. However, due to the complex depositional environments, there have been few reports on the quantitative evaluation of lacustrine pores. In this study, we carry out experiments, e.g., scanning electron microscopy (SEM), nitrogen adsorption, X-ray diffraction (XRD), and rock pyrolysis, on sixteen lacustrine shale core samples of the Late Cretaceous Nenjiang Formation (K2n1+2) in the Songliao Basin. At the same time, we bring in the fractal dimensions to quantitatively characterize the pores of shale samples in K2n1+2. The kerogen type of shales in the Nenjiang Formation is mainly type Ⅰ. The shales of K2n1+2 develop a large number of mineral intergranular pores and a small number of organic pores and mineral intragranular pores. The primary minerals of the samples are clay minerals and quartz. The total organic carbon (TOC) has a correlation with the pore physical parameters, whereas the content of minerals does not correlate significantly with pore development. The average pore fractal dimensions obtained from the analysis of nitrogen adsorption data are D1 = 2.5308 and D2 = 2.6557. There is a significant negative correlation between the fractal dimensions (D1 and D2) and the TOC content: the lower the fractal dimensions, the higher the TOC, and the more the free oil. In low maturity shales with higher TOC content, due to hydrocarbon generation, larger pores with a regular shape (small fractal parameters) can be produced, which can store more free oil. The shale reservoir evaluation of K2n1+2 in the Songliao Basin should be focused on shales with higher TOC and lower pore fractal parameters. Our work provides a reference for the shale oil evaluation of K2n1+2 in the Songliao Basin and complements studies on lacustrine pore characteristics.